Closed-Form Approximation of LoRa Modulation BER Performance - Elshabrawy, Tallal; Robert, Jörg (IEEE Communications Letters, 2018)
LoRa has been demonstrated as a front runner when it comes to evolving low-power wide area networks. At its core is LoRa modulation which depicts a patented chirp spread-spectrum modulation technique that supports energy-efficient and reliable long-range communication. The underlying bit error rate (BER) performance of LoRa modulation has not been yet rigorously analyzed in the literature. In this letter, closed-form approximations for LoRa BER performance are derived for both additive white Gaussian noise and Rayleigh fading channels. Accuracy of the derived approximations is confirmed by comparisons against numerical results.
CRIS-Team Scopus Importer:2024-11-19
Keywords: BER performance analysis; chirp modulation; LoRa; LP-WAN; spread spectrum